Utilization of Silica Fume, Fly Ash, Rice Husk Ash as SCMs (A Tertiary Mix) in Plastic Aggregate Concrete (International Journal of Innovative Research in Engineering & Management, 2022)
For sustainable development and protection  of environment, plastic reuse is the best alternative for plastic  waste management. Over the years extensive research has  been carried out on the use of plastic in civil constructions.  Also, the main challenges in the construction sector are  caused by the Portland cement production. The obvious,  basic and suitable solution is the less consumption of the  same and by partial replacement of cement by SCMs  (supplementary cementitious materials). Though utilization  of plastic waste, fly ash, rice husk ash, silica fume and  reduction in cement usage is advantageous from  environmental point of view but their properties and behavior  together as a construction material requires extensive  investigation.In this study, keeping in view the environmental effects  caused by the plastic wastes, cement production, various  industrial and agricultural wastes; an investigation has been  carried out to study the effect of partial replacement of  cement by three different wastes i.e., Silica Fume, Fly Ash  and Rice Husk Ash in combined proportions along with  partial coarse aggregate replacement with plastic waste and  to obtain optimum proportions of waste replacement. The  research is carried out in two stages. In the first stage only  the binder/cement is focused upon and replaced by different  percentages in combined proportions of SF, FA and RHA. It  was found out that the optimum percentage of cement  replacement is 40% in which combined proportion is  (10%SF, 10%RHA, 20%FA). In the second stage, the (10%SF, 10%RHA, 20%FA)  replacement of cement is kept constant and the natural coarse  aggregate is replaced by PP Plastic in proportions 20%, 30%  and 40% respectively. Consequently, the optimum  proportion of plastic was found to be 20% for the cement  replaced plastic induced concrete (CRPIC).  Physical characteristics of this cement replaced plastic induced concrete (CRPIC) were determined by compressive  strength tests, flexural tests, slump test. The chemical and  water absorption properties along with weight of hardened  concrete was assessed and the latter was compared with  traditional concrete. This research, in general, will decrease  the amount of natural coarse aggregate and cement quantity  that are used in the construction industry and will  consequently reduce the waste that is disposed into the  surroundings.
Keywords: CRPIC–Cement Replaced Plastic- Induced concrete; FA – Fly Ash; NA – Natural Aggregate; OPC – Ordinary Portland Cement; PA – Plastic Aggregate; PAC – Plastic Aggregate Concrete; RHA – Rice Husk Ash; SCM – Supplementary Cementitious Material; SEM – Scanning; Electron Microscopy; SF – Silica Fume; XRD – X Ray Diffraction